Non-invasive assessment of thrombolysis results in acute myocardial infarction: electrocardiogram dynamics of ST segment elevation and T wave - L. L. Berstein (Российский кардиологический журнал, 2007)
The assessment of reperfusion effectiveness in acute myocardial infarction (AMI) is an important clinical task. In 106 AMI patients with ST elevation, the dynamics of ST segment and Twave was analyzed using the data of three electrocardiograms (baseline, 3 and 48 hours after thrombolysis - ECG-1, 2, and 3, respectively). Separately for anterior and поп-anterior AMI, ST decrease degree in the lead with its maximal elevation (STmax decrease aAMI, naAMI), as well as decrease in total ST elevation in all leads with its elevation (STsum decrease aAMI, naAMI) were analyzed. Other parameters calculated included summary T wave amplitudes in leads with ST elevation on ECG-2 and ECG-3 (sumT2, sumT3), their difference between ECG-2 and ECG-3 (sumT2-sumT1) or between ECG-3 and ECG-1 (sumT3-sumT1). Reperfusion effectiveness was assessed by local left ventricular contractility index reduction 10±3 days after thrombolysis. Sensitivity and specificity of these criteria, with calculated cut-off levels, were as follows: sumT3-sumTl?28*: 68 and 76 %; STsum decrease aAMI >44, 0 % - 81 and 62 %; STsum decrease naAMI >58, 8 %* - 100 and 42 %; STmax decrease naAMI>66, 7 %* - 83 and 53 %; STmax decrease aAMI>33, 3 %* - 81 and 54 %; sumT3<10* - 98 and 30 %; sumT2-sumT1?28* - 39 and 86 %; sumT2<14 -75 and 43 % (*p<0, 05). Analyzing simple electrocardiography parameters could facilitate the assessment of myocardial reperfusion effectiveness in AMI.